Rancang Bangun Aplikasi Absensi Karyawan menggunakan QR-Code Berbasis Web pada SMA Candra Naya - Sutisna; Akbarulloh, Fery; Wahyudi, Ahmad Arif; Banase, Samuel Figo; Simarmata, Nuary Inaldy (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
This research discusses the development of a web-based employee attendance application using the waterfall method at SMA Candra Naya. The waterfall method was chosen due to its organized structure, starting from requirement analysis to maintenance. The stages involved include requirement analysis, design, implementation, testing, and maintenance. The application utilizes QR-code technology as a unique identification tool for employees, enabling efficient and accurate attendance processes. Evaluation was conducted through internal testing at SMA Candra Naya to assess the performance and reliability of the application. The evaluation results indicate that the application successfully enhances the efficiency of attendance administration and simplifies employee attendance management. The primary contribution of this research is the application of the waterfall method as a systematic approach in developing web-based applications for employee attendance management, which can be adopted by educational institutions and similar organizations to improve the efficiency and accuracy of attendance processes.